Experimental evaluation of acceleration waveform replication on electrohydraulic shaking tables: A review. (18th October 2016) - Shen, Gang; Zhu, Zhencai; Li, Xiang; Li, Ge; Tang, Yu; Liu, Shanzeng
An electrohydraulic shaking table is an essential experimental facility in many industrial applications to real-time simulate actual vibration situations including structural vibration and earthquake. However, there is still a challenging area for its acceleration waveform replication because acceleration output responses of the electrohydraulic shaking table would not be as intended in magnitude and phase of an acceleration closed-loop system due to inherent hydraulic nonlinear dynamics of electrohydraulic servo systems. Thus, how to accurately and coordinately control parallel hydraulic actuators of the electrohydraulic shaking table is a critical issue; so, many control techniques have been developed to address the issue. Some currently used key techniques in this field are reviewed in the article, which are the objectives of academic investigations and industrial applications. The article reviews some new control algorithms for the electrohydraulic shaking table to obtain high-fidelity acceleration waveform replication accuracy.